Development of an Integrated Physics Problem-Solving Model in Virtual Media for Class XI Students - Astuti, Wahyu Indah Widya; Hermansyah, Hermansyah; Fitriyanto, Syarif; Yahya, Fahmi; Nisyah, Mir'atun (Physics Education Research Journal, 2025)
This research and development aims to determine the feasibility of developing problem-solving-based learning tools assisted by virtual media. The type of research used is Research and Development (R&D) with the ADDIE model (analysis, design, development, implement, evaluate), which is only carried out up to the development stage. The subjects of this research were physics teachers and students of class XI IA MAN 1 Sumbawa for the 2022/2023 academic year. The research instrument uses a questionnaire for material experts, media, practitioners, and students. The instruments used were validation questionnaire sheets and student response questionnaires to determine the feasibility of problem-solving-based learning tools assisted by virtual media. Based on the results of expert validation and product trials, it shows that the product quality has reached the appropriate standards for learning media. Material expert validation obtained an average percentage result of 96.67% with the criteria "very feasible". Media expert validation obtained an average percentage result of 95.14% with the criteria "very feasible". The teacher practitioner test obtained an average percentage result of 100% with the criteria "very good". The limited trials obtained an average percentage result of 88.22% with "very good" criteria. The results of the effectiveness test obtained an average percentage of 90.45% with the criteria "very good". Based on the results of the description above, the product developed, namely a problem-solving-based learning device assisted by virtual media, is said to be suitable for use in learning in Class XI IA.